Nuclear Legislation in OECD Countries: Mexico - Organisation for Economic Co-operation and Development; Nuclear Energy Agency (Paris OECD Publishing, 2006)
This publication provides comprehensive information on the regulatory and institutional frameworks governing nuclear activities in Mexico. It examines the general regulatory regime, including mining, radioactive substances and equipment, nuclear installations, trade in nuclear materials, radiation protection, radioactive waste management, non-proliferation and physical protection, transport, and nuclear third party liability; and has another section covering the institutional framework including regulatory and supervisory authorities, advisory bodies, and public and semi-public agencies
Keywords: Nuclear Energy; Mexico